Analisis Pengaruh ADD, IPM, Dan Jumlah Tenaga Kerja Terhadap Pertumbuhan Ekonomi Kabupaten Lamongan - Dicky Angga Nugraha Pradana; Dwi Susilowati (Program Studi Ekonomi Pembangunan Universitas Muhammadiyah Malang, 2022)
The purpose of this research is to analyze the effect of village fund allocation, human development index, and number of workers on economic growth. This research was conducted in Lamongan Regency. The results of this research shows that simultant test (F-test all independent variables had an effect on Economic Growth. The results of the partial test (t-test) show that the Village Fund Allocation has a positive and insignificant effect on Economic Growth, the Human Development Index has a significant negative effect on Economic Growth. While the number of workers has a significant positive effect on economic growth.